Performance, Perceptual and Reaction Skills and Neuromuscular Control Indicators of High-Level Karate Athletes in the Execution of the Gyaku Tsuki Punch - Goethel, Márcio Fagundes; Vilas-Boas, João Paulo; Machado, Leandro; Ervilha, Ulysses Fernandes; Moreira, Pedro Vieira Sarmet; Bendilatti, Antonio Roberto [UNESP]; Hamill, Joseph; Cardozo, Adalgiso Coscrato [UNESP]; Gonçalves, Mauro [UNESP] (MDPI, 2023)
This study aimed to investigate and compare the performance, perceptual and reaction skills and neuromuscular control indicators of sub-elite (SEG) and elite (EG) karate athletes during the execution of a Gyaku Tsuki punch. The study included 14 male athletes, equally divided into two subgroups according to their current competitive level. We analyzed the peak and mean linear velocity of the wrist, linear peak acceleration/deceleration of the wrist, braking time, pre-motor time, motor time, reaction time, movement time and co-contraction index between selected muscle groups. EG athletes presented higher values in almost all performance variables, with the exception of the mean linear velocity of the wrist, which was similar between the groups. In the perceptual and reaction skills, the EG athletes presented shorter time durations with the exception of the pre-motor time, which did not reveal significant differences. The only significant difference in the indicators of neuromuscular control were found during the deceleration phase, where the EG athletes presented a higher co-contraction index between the biceps brachii and the triceps brachii. In conclusion, the EG athletes, in addition to being faster to react, faster to accelerate the wrist, could perform the braking in less time than the SEG athletes, making the technique less perceptible to the opponent.
Keywords: electromyography; kinematics; martial arts; punch; reaction time